Pengaruh Baby Massage Terhadap Kualitas Tidur Dan Kenaikan Berat Badan Pada Bayi Usia 3-12 Bulan - Imadilla, Nadine Ringgy Ayu; Hastuti, Apriyani; Kurniawan, Ardhiles Wahyu (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Baby massage has been gaining popularity recently for its ability to promote healthier, less fussy babies. It can also strengthen muscles, boost immunity, increase weight gain, reduce pain, and promote deeper sleep. Objective This research To determine the effect of baby massage on sleep quality and weight gain in babies aged 3-12 months in PMB mrs. E Kelurahan Jogotrunan Lumajang Method In this study, employed a quasi-experimental research plan with a pre-post-test control group design. Experimental research is a research design used to establish causal relationships by involving researchers in manipulating independent variables. The research design used was a pre-test and post-test experimental study with a control group that began from December 24, 2024, to January 28, 2025. The population in this study were college 40 babies aged 3-12 months in Jogotrunan sub-district, Lumajang Regenc, the data from the examination results are analyzed using univariate and bivariate analysis. Results : Research results in the experimental group (pretest) showed that most respondents had sleep quality <9 hours, namely 12 respondents (60%), while in the treatment group after (posttest) most respondents had sleep quality >9 hours, namely 16 respondents (80%). In the control group (pretest) most respondents had sleep quality <9 hours, namely 11 respondents (55%), while in the control group after (posttest) some respondents had sleep quality >9 hours, namely 12 respondents (80%). Meanwhile, in the experimental group (pretest), most respondents had a steady weight gain of 11 respondents (55%), while in the experimental group after (posttest), some respondents had a steady weight gain of 15 respondents (75%). In the control group (pretest), most respondents had a steady weight gain of 12 respondents (60%), while in the control group after (posttest), some respondents had a steady weight gain of 11 respondents (55%). Conclusion There is an influence of baby massage on sleep quality and weight gain in infants aged 3-12 months at pmb ny. e, jogotrunan village, lumajang regency, This information can be a basis for providing guidance to parents or nurses regarding the importance of baby massage in improving sleep quality and weight gain in babies aged 3-12 months.